Biomass waste carbon materials for post-combustion CO2 capture - Calvo-Muñoz, Elisa Maria; García-Mateos, Francisco José; Rosas-Martínez, Juana María; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (Asociación Nacional de Químicos de España, 2016)
Low-carbon energy systems based on carbon capture and storage (CCS) have become of great interest due to the imperative necessity of mitigating the carbon footprint derived from the currently fossil fuels-based energy technologies. In this sense, post-combustion CO2 adsorption over porous solids results particularly attractive from several viewpoints. In a green context, the use of carbon-based materials as adsorbents would entail important economic and environmental profits, such as the valorization of different types of biomass and lignocellulosic waste. In this work, six carbon materials were prepared from four types of low cost biomass residues. Electrospun carbon fibers, FCL, and a char, GCL, were obtained from Alcell® lignin. Two activated carbons, GAS and GAWBa, resulted from physical activation of olive stones and plywood waste, respectively. Finally, another activated carbon, GAL, and an activated carbon cloth, CAD, were synthesized by chemical activation of lignin and a denim cloth. These materials were evaluated as potential adsorbents for CO2 capture under post-combustion conditions by means of equilibrium and dynamic experiments (fixed-bed system). Moreover, the regeneration capacity of the samples was also studied. At 101.3 kPa, the samples displayed CO2 capacities between 2.0 and 3.1 mmol/g. Meaningfully, the uptake values, at typical CO2 pressures in post-combustion applications (c.a. 15 kPa), remain in the range of 0.7 to 1.2 mmol/g, which are comparable to those of other complex and appealing materials. Additionally, a thorough characterization of the porous structure of the different adsorbents provided new insights into the influence of the pore size distribution on the CO2 capture capacity. CO2 retention capacities correlate well with the narrow micropore volume derived from the CO2 adsorption data at 0 ºC, VDRCO2, at 101.3 kPa (Figure 2). In contrast, at 15 kPa, analysis of the cumulative pore volumes of the samples pointed out that only pores of sizes below 0.7 nm are relevant for adsorption. Under dynamic conditions, the studied materials also showed remarkable adsorptive behaviors. For instance, the lignin-derived carbon fiber (FCL) exhibited a capacity value higher than 1.3 mmol/g.
Keywords: Biomasa; Energía de biomasa; CO2 capture; Post-combustion; Adsorption; Biomass; Carbon materials